Thinking faith after Christianity : a theological reading of Jan Patočka's phenomenological philosophy - Kočí, Martin, 1987- (Suny series in theology and continental thought, 2020)
"This book examines the work of the Czech Philosopher Jan Patočka from the largely neglected perspective of religion. Patočka is known primarily for his work in phenomenology and ancient Greek philosophy, and also as a civil rights activist and a critic of modernity. He also maintained a persistent and increasing interest in Christianity, Martin Koci shows, and indeed his first and last publications concerned religion and theology. This book examines the theological motifs in Patočka's work, and brings his thought into discussion with recent developments in phenomenology, making a case for Patočka as a forerunner to what has become known as the theological turn in continental philosophy. Koci systematically examines his thoughts on the relationship between theology and philosophy, and his perennial struggle with the idea of crisis. For Patočka, modernity, metaphysics, and Christianity were all in different kinds of crises, and Koci demonstrates how his work responded to those crises theologically. Thinking Faith after Christianity thus provides new insights on theology understood as the task of thinking and living transcendence in a problematic world. It perceives the un-thought element of Christianity - what Patočka identified as its greatest resource and potential - not as a weakness, but as a credible way to ponder Christian faith and the Christian mode of existence after the proclaimed death of God and the end of metaphysics"--